2010
DOI: 10.1007/s00428-010-1005-6
|View full text |Cite
|
Sign up to set email alerts
|

The role of radiological–pathological correlation in diagnosing early breast cancer: the pathologist’s perspective

Abstract: Early breast carcinoma, defined as purely in situ cancer and invasive carcinomas < 15 mm, represents the most frequent category of breast carcinomas in diagnostic routine in a regularly screened population. These tumors are usually detected with mammography screening and are preoperatively characterized with radiological imaging. The role of pathology in preoperative settings is to help understand the subgross morphology and to confirm malignancy in biopsy material. Postoperatively, the pathologist needs to ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Mammography is the gold standard modality for detecting microcalcifications [19]. BI-RADS 3–5 microcalcifications are a characteristic appearance of breast cancer at mammographic imaging and a well-known criterion in the diagnosis of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mammography is the gold standard modality for detecting microcalcifications [19]. BI-RADS 3–5 microcalcifications are a characteristic appearance of breast cancer at mammographic imaging and a well-known criterion in the diagnosis of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…The characteristics of breast microcalcifications continue to attract interest. Hashimoto and coworkers found that patients with microcalcifications were significantly more likely to have LN metastases [19]. Li and coworkers found that malignant-appearing microcalcifications were significantly associated with a LN (+) status and that they always presented in breast cancer patients who were non-menopausal as well as with a family history of carcinoma [22].…”
Section: Discussionmentioning
confidence: 99%
“…Modern multimodality breast radiology is very accurate in determining the subgross morphological prognostic parameters [7]. It uses different imaging modalities for the same lesion, which when combined can compensate for the limitations of the results of the individual methods.…”
Section: Radiological-pathological Correlation In the Multimodalitmentioning
confidence: 99%
“…Th e method of large-format histology sections is not per se suffi cient for adequate assessment of the radiological-surgical parameters. Detailed and systematic radiological -pathological correlation is also necessary [14][15][16][17]. Th e radiological imaging methods, especially if used in combination (multimodality approach) are very sensitive in preoperative assessment of tumour size, lesion distribution, disease extent and position of the lesions, but histological confi rmation of the radiological fi ndings is essential because the radiological methods are somewhat less specifi c than sensitive in diagnosing breast lesions [16,17], as illustrated in Fig.…”
Section: Large-format Histopathologymentioning
confidence: 98%
“…Th is is the reason why many breast experts are reluctant to recognise the importance of breast cancer multifocality and disease extent; the principal that the things we (or our pathologists) do not see -do not exist. Th is destructive attitude is not acceptable in the era of modern radiological investigations and alternative histological methods able to demonstrate the real distribution of the lesions and the real disease extent of breast carcinomas [14][15][16][17][18][19].…”
Section: The Limitations Of the Conventional Pathologic Workupmentioning
confidence: 99%